Nonhydrolyzable C-disaccharides, a new class of DC-SIGN ligands - Bertolotti, Benedetta; Oroszová, Beáta; Sutkeviciute, Ieva; Kniežo, Ladislav; Fieschi, Franck; Parkan, Kamil; Lovyová, Zuzana; Kašáková, Martina; Moravcová, Jitka (Carbohydrate research, 2016)
The discovery of effective ligands for DC-SIGN receptor is one of the most challenging concepts of antiviral drug design due to the importance of this C-type lectin in infection processes. DC-SIGN recognizes mannosylated and fucosylated oligosaccharides but glycosidic linkages are accessible to both chemical and enzymatic degradations. To avoid this problem, the synthesis of stable glycoside mimetics has attracted increasing attention. In this work we establish for the first time mono- and divalent C-glycosides based on d-manno and l-fuco configurations as prospective DC-SIGN ligands. In particular, the l-fucose glycomimetics were more active than the respective d-mannose ones. The highest affinity was assessed for simple 1,4-bis(α-l-fucopyranosyl)butane (SPR: IC50 0.43 mM) that displayed about twice higher activity than natural ligand Le(x). Our results make C-glycosides attractive candidates for multivalent presentations.
Keywords: Biomimetics; receptory buněčného povrchu; biomimetika; lektiny typu C; mannosa; Cell Adhesion Molecules; Mannose; Molecular Structure; glykosidy; Humans; Lectins, C-Type; lidé; Glycosides; molekuly buněčné adheze; fukosa; Receptors, Cell Surface; Fucose; molekulární struktura